Advanced Cluster Based Spectrum Sensing in Broadband Cognitive Radio Network - Jothi, T; Panimalar, P (International Journal of Computer Sciences and Engineering, 2025)
A radio spectrum higher data rates is a challenging task that requires inventive advances prepared for giving better methodologies for using the open radio spectrum. The issue of applying the Cognitive radio technique successfully is how to sense exactly and quickly whether or not the Primary User (PU) exists, and searching for the spectrum holes to provide the Secondary User (SU). The proposed system focus on Advanced Cluster Based Spectrum Sensing (ACBSS) algorithm which combines hierarchical data-fusion idea with jointly compressive reconstruction technology. To validate the efficiency and effectiveness, we compare the ACBBSS with Independent Compressive Sensing (ICS) and Joint Compressive Sensing (JCS) in the detection probability, false-alarm probability and algorithm execution time under the situation of unusual SNR and compression ratio. The majority of existing work has focused on Single band Cognitive Radio, multiband cognitive radio represents great promises toward implementing efficient cognitive networks compared to single-based networks. This has primarily motivated the introduction of Multiband Cognitive Radio (MB-CR) paradigm, which is also referred to wideband CR. In addition, it helps contribute seamless handoff from band to band, which get better the link maintenance and reduces data transmission interruptions